Optimalisasi Portofolio Kredit untuk Perencanaan Ekspansi Kredit pada Perbankan Nasional: Credit Portfolio Optimization for Credit Expansion Planning on National Banking - Rini Siswati Asnel; Lukytawati Anggraeni; Amzul Rifin (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The aim of this study is to determine the portfolio performance in each economic sector based on return and risk of portfolio credit at 3 Sentra Kredit Menengah (SKM) under BNI WJS supervision and to find out the optimal combination or composition of the loan portfolio that provides the greatest return and the lowest risk. In this study using the Markowitz model to produce an optimal portfolio combination. The results showed recommendations of portfolio for the Jakarta Senayan Jakarta Regional especially for SKM, it was suggested to management to expansion in sectors or business with their competencies. To plan the optimal composition of the loan portfolio for credit expansion plan, the alternative of optimum portfolio from the results of this study can be used as a reference. Keywords: loan portfolio, markowitz model, Sentra Kredit Menengah (SKM) , return, risk credit